The Analysis of the Significance of the Influence of Work Culture, Work Environment, and Social Capital on Teacher Resilience in Islamic Educational Institutions in Malang - Sutrisno, Sutrisno; Wan Mohamad Nazarie, Wan Nur Fazni binti; Mohd Radzi, Fatin Aliana; Musnandar, Aries; Dalle, Abd. Rahman Ambo' (J-MPI (Jurnal Manajemen Pendidikan Islam), 2025)
This research explores the significant role of work culture, work environment, and social capital in shaping teacher resilience within Islamic educational institutions in Malang, Indonesia. Teachers in these settings face the dual challenge of academic responsibility and the need to instill Islamic values, making resilience a crucial factor for their professional success. The study employs a quantitative approach, using a structured survey to gather data from 70 teachers across various Islamic schools in Malang. Data analysis was performed using ordinal logistic regression (OLR). The analysis reveals that a positive work culture, which integrates Islamic ethical principles, plays a critical role in enhancing teacher resilience. Additionally, a supportive work environment, both physically and socially, is essential for mitigating stress and fostering well-being. In contrast, social capital, while valuable, does not show a statistically significant impact on teacher resilience in this study. These findings underline the importance of nurturing supportive work environments and promoting Islamic values to bolster teacher resilience, ultimately contributing to improved educational outcomes in Islamic schools.